MOTIF PERILAKU BIBLIOCRIME DI UPT PERPUSTAKAAN UIN RADEN FATAH PALEMBANG - Linda Maryani; Herlina Herlina (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2019)
Introduction.This study aimed to determine the behavioral motives of bibliocrime in Library of UPT Raden Fatah Palembang. This study aims to find out what the motives of the user do bibliocrime, how the impact and prevention efforts have been made by the library. Data Collection Method. Methods of data collection using observation, interview and documentation techniques. Analysis Data. (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing. Results and Discussions. The results showed that the backgrounds motive of user doing bibliocrime was based on the need to fulfill lecture assignments and final assignments, self-actualization, overflowing hatred, wanting to utilize collections exclusively for personal interests, expensive photocopying fees, difficulty finding collections, collections which cannot be loaned, collections that are in demand, collections that are stagnant, forgotten, lazy and have a certain busyness. UPT Raden Fatah Library UPT Palembang have two losses experienced are social losses and financial losses. Social losses in the form of poor library images. While financial losses, the library must replace lost and damaged collections. The three prevention efforts that have been carried out by UPT Raden Fatah Library of Palembang are installing CCTV, security gates, and user education. Conclution. Based on the findings, the backgrounds motive of user doing bibliocrime in UPT Raden Fatah Library UPT Palembang, They have two losses experienced, and they have three efforts to prevention of bibliocrime. Keywords: Bibliocrime, motive, Library of UIN Raden Fatah Palembang.